1996
DOI: 10.1111/j.1365-2672.1996.tb03559.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and level of Listeria monocytogenes contamination of food sources at primary production and initial processing

Abstract: Listeria monocytogenes was isolated in low numbers from a variety of environmental samples associated with the primary production of food, including vegetation, faeces and meat. The organism was rarely detected on growing grass and vegetables prior to processing. The excretion of L. monocytogenes by farm animals was linked to their diet, with animals fed entirely on hay or manufactured diets not excreting detectable levels of Listeria (i.e. absence in 25 g). However, animals fed on silage, which is frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 25 publications
5
126
0
9
Order By: Relevance
“…The prevalence in grilled samples is associated with inadequate heat treatment (Passos & Kuay, 2002), while the prevalence in meat that was cooked with sauce, whose cooking time is greater, is associated with poor maintenance or inadequate reheating. Fenlon et al, 1996, observed that the prevalence of Listeria spp. in meat and meat products may be attributed either to improper hygienic practice during processing or to food handlers.…”
Section: B)mentioning
confidence: 99%
“…The prevalence in grilled samples is associated with inadequate heat treatment (Passos & Kuay, 2002), while the prevalence in meat that was cooked with sauce, whose cooking time is greater, is associated with poor maintenance or inadequate reheating. Fenlon et al, 1996, observed that the prevalence of Listeria spp. in meat and meat products may be attributed either to improper hygienic practice during processing or to food handlers.…”
Section: B)mentioning
confidence: 99%
“…In the literature, the detection of the L. monocytogenes pig batch status has been more frequently described by means of samples taken at the slaughterhouse. Sampling methods were either individual coprology [1,14,40,42], tonsillar swabbing [26] or skin swabbing [11] on a sample of pigs. The ability of the skin swabbing method to detect L. monocytogenes contamination of pigs has already been demonstrated [11].…”
Section: Discussionmentioning
confidence: 99%
“…It was early suspected that growing pigs were resistant to L. monocytogenes infection [6]. Since then several reports have mentioned that L. monocytogenes is asymptomatically carried by the pigs [1,5,14,23,26,40,43].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the application of raw animal manure for fertilizer increases the threat of contamination on fruits and vegetables ( Brackett, 1992). Direct or indirect pathogen contamination of fresh produce can occur at many points in the production chain during growth and processing (Fenlon, et al, 1996; Beuchat and Ryu. 1997), thus presenting a food safety challenge to consumers.…”
Section: Wwwintechopencommentioning
confidence: 99%